Identification of Heavy Metal Plumbum (Pb) in Edible Offal - Ellin Harlia; Roostita L.Balia; Denny Suryanto (Fakultas Peternakan, Universitas Padjadjaran, 2017)
Plumbum (Pb) is a heavy metal that its presence is undesirable because it can lead to the formation of residues in animal or human body which cause health problems. Pb source can be derived from disinfectant, bedding materials, corrosion equipment, paint, animal feed, water and soil. Livestock farming is difficult to avoid Pb contamination, so it is important to do research on the identification of Pb in edible animal offal (pig liver, beef cattle tripe and lamb kidney). This research is an exploratory study on 12 samples of pig liver, 12 samples of beef cattle tripe and 12 samples of lamb kidney which sold in the traditional market in Bandung, the samples were analyzed using AAS machine at Balai Penelitian Veteriner in Bogor, data were analyzed descriptively. The results showed that 50% of beef cattle tripe contains residues of heavy metals Pb, accounted 0.98 ppm on average, while all samples of pig liver and lamb kidneys contain residues of heavy metals Pb with average residues 0.35 ppm and 0.50 ppm, respectively. This condition is safe because it below the MRL (Maximum Residue Limits) established by SNI which is 1.00 ppm.